Canada's RMC : a history of the Royal Military College. - Preston, Richard A., 1910-2006 (History of the Royal Military College of Canada, 1969)
Professor Preston trances the turbulent career of the Royal Military College of Canada from its beginnings, through the political upheavals of the 1800s and the following years when it was reformed to produce an important nucleus of the Canadian Expeditionary Force officer corps in World War I.